Comparative analysis of Egypt's malaria elimination strategies and implementation science: Pathways to achieve malaria-free status for other African countries. - Chukwuka Elendu; Dependable C Amaechi; Rhoda C Elendu; Sehajmeet Kaur Saggi; Tochi C Elendu; Emmanuel C Amaechi; Ijeoma D Elendu; Kanishk Dang; Opeyemi P Amosu; Omoyelemi F Idowu; Toluwanimi S Oseni (PLoS ONE)
Background Malaria elimination is a critical public health goal, particularly in Africa, where the disease disproportionately affects vulnerable populations. Egypt's success in achieving World Health Organization (WHO) malaria-free certification on October 20, 2024, through an evidence-based malaria elimination program, offers a valuable model for replication. Our study is identified as an implementation study, evaluating the evidence-based interventions deployed, the implementation strategy tested, and its outcomes to provide insights for scaling similar programs across Africa. A RE-AIM-informed lens was applied to better articulate how contextual factors, intervention reach, effectiveness, adoption, implementation, and maintenance influenced observed outcomes. Methods We adopted a retrospective implementation science approach to analyze Egypt's malaria elimination program. The implementation strategy focused on high-priority malaria-endemic regions, targeting vulnerable groups such as children under five and pregnant women. Interventions included vector control measures, such as insecticide-treated nets (ITNs), indoor residual spraying (IRS), antimalarial treatment protocols, and public health education campaigns. Key implementation strategies included workforce training, multilevel stakeholder engagement, integrated data-driven decision-making, and community mobilization. Our study evaluated key implementation outcomes, including fidelity, feasibility, acceptability (measured using a custom-designed tool assessing stakeholder and community perceptions of the interventions), and adaptability alongside health outcomes such as incidence reduction, treatment coverage, and community awareness. Economic evaluations and process analyses provided additional insights into cost-effectiveness and operational efficiency. Results The implementation strategy targeted malaria-endemic regions, achieving a 92% recruitment rate, focusing on vulnerable groups such as children under five (37%) and pregnant women (12%). 78% of the recipient population adhered to preventive measures like insecticide-treated nets (ITNs). The program reduced malaria incidence by 96% over 15 years and achieved a 94% reduction in Anopheles mosquito density. Active surveillance led to the detection of 98% of cases within 48 hours of symptom onset, while treatment coverage reached 91%. Community awareness of malaria prevention increased to 84% by the program's conclusion. Economic evaluations revealed a cost per disability-adjusted life year (DALY) averted of $24, with an estimated $1.5 billion saved in healthcare costs and productivity losses over 15 years. Sub-group analyses highlighted higher adherence rates in urban areas (89%) compared to rural areas (73%) and significant reductions in malaria-related complications among pregnant women (78%). Implementation outcomes included high fidelity (93%) to planned strategies, high feasibility across urban and rural contexts, and successful adaptability to emerging challenges such as insecticide resistance and funding fluctuations. Routine monitoring systems, continuous feedback loops, and responsive adaptation mechanisms were central to achieving these outcomes. Acceptability scores averaged 87% across stakeholders, reflecting strong alignment with community values, trust in health authorities, and perceived relevance of interventions. Conclusion Egypt's malaria elimination strategies exemplify the effective integration of implementation science into public health programs. Key success factors included community engagement, robust surveillance systems, and cost-effective resource allocation. The intentional use of implementation strategies and documented outcomes demonstrate alignment with the RE-AIM framework, reinforcing the program's relevance for broader application. Future efforts should emphasize tailored interventions, capacity building, transparent assessment of acceptability, and sustainable funding mechanisms to replicate Egypt's success.